Rare case of gastric extranodal marginal zone lymphoma - Raina, Devisha (International Surgery Journal, 2021)
True histiocytic lymphoma is considered a rare entity, and its diagnosis requires the concordance of morphological, immunophenotypic, and molecular findings. Gastric extra nodal marginal zone B-cell lymphoma of mucosa-associated lymphoid tissue (MALT) is a B-cell non-Hodgkin lymphoma that arises in the stomach and has a perifollicular/marginal zone growth pattern. The lymphoma is derived from marginal zone B-cells and recapitulates the architecture and organization of native MALT exemplified by the Peyers’ patches in the terminal ileum. Marginal zone lymphoma of MALT (MALT lymphoma) is the most common indolent subtype and represents 7% of all non-Hodgkin lymphomas.